PREVENTION OF OBSTETRIC COMPLICATIONS IN WOMEN WITH B VITAMIN DEFICIENCY - Mischenko, V.P.; Rudenko, I.V.; Likhachov, V.K.; Golubenko, M.Y.; Dobrovolska, L.M. (World of Medicine and Biology, 2019)
Findings of the studies made in the group of women of reproductive age with B vitamin deficiency, who received comprehensive preventive maintenance and treatment of gestational complications supplemented with vitamin therapy have been presented. The data of comparative characteristics of clinical and laboratory observations with a group of women who received conventional therapy have been elucidated. The efficiency of application of the suggested etiopathogenetic approach aimed at prevention maintenance and comprehensive therapy of gestational complications have been grounded.